Posted by Rahul Solanki 1 year, 7 months ago
Let X = Y
Multiply Y both sides,
Subtract X2 both sides,
So, XY - X2 = Y2 - X2 ,
This will be, X(Y-X) = (Y-X) (Y+X),
now (Y-X) cancel out both sides....
so, X = Y+X
( As we let above X=Y, so we can replace Y to X ),
so, X = X + X
. X = 2X
now,. X/X = 2,
And this will be ((( 1= 2 )))...!!!!!!!!!!!! How is this possible , I am still confused?????
Posted by Mintu Rawat 2 years, 4 months ago
Subscribe complete study pack and get unlimited access to selected subjects. Effective cost is only ₹ 12.5/- per subject per month. Based on the latest CBSE & NCERT syllabus.
Create papers in minutes
Print with your name & Logo
Download as PDF
3 Lakhs+ Questions
Based on CBSE Blueprint
Best fit for Schools & Tutors
No software required, no contract to sign. Simply apply as teacher, take eligibility test and start working with us. Required desktop or laptop with internet connection